Menyingkap Kelayakan Rencana Bisnis Atas Pemanfaatan Aset Tetap Berupa Tanah Milik Pemerintah Pusat - Nurbiyanto, Nurbiyanto; Rahmanto, Dwi (Polytechnic of State Finance STAN, 2023)
State-owned Assets (BMN) is an asset owned by the state that must be managed optimally. Optimal BMN management can be seen from a financial and non-financial perspective. From a financial perspective, BMN optimization provides financial input in the form of Non-Tax State Revenue (PNBP), while for non-financial optimization, BMN is used optimally by statutory provisions. This study attempts to outline the steps and calculations to determine the financial feasibility of managing BMN. BMN management is carried out in the form of utilization through utilization cooperation with potential investors. The research object is BMN in the form of empty land belonging to the Ministry of Education, Culture, Research, and Technology. A quantitative approach is used to analyze the feasibility of BMN management. Data uses primary data, secondary data, and other documents related to business plans. Data collection was carried out using field observations, interviews with potential investors, and studies via the Internet. Apart from that, the article is also based on literature studies to explore the BMN management process in the form of cooperation in utilizing BMN. The analysis concludes that BMN's business feasibility plan from the business project side is feasible, from the investor's financial side it is also feasible, while from the government side, it gets adequate capitalization.